Motivational Interviewing among HIV Health Care Providers: Challenges and opportunities to enhance engagement and retention in care in Buenos Aires, Argentina - Bofill, Lina (J Int Assoc Provid AIDS Care, 2015)
Providers’ response to Motivational Interviewing (MI) to improve engagement and retention in care among challenging patients with HIV in Argentina were evaluated. 12 HIV care physicians participated and video recordings pre- and post-MI training were obtained. One week post-training 11/12 participants were committed to using MI strategies during consult session. 9/12 participants demonstrated appropriate utilization of MI techniques and increased adherence focused discussion and care (t = 3.59, p = .006). MI appears to be a viable strategy to enhance engagement and retention in challenging HIV patients.